Diagnosis and Workup of Intellectual Disability in Adults: Suggested Strategies for the Adult Neurologist. Issue 6 (December 2021) - Frueh, Julia Sophie; Press, Daniel Zvi; Sanders, Jessica Solomon
Abstract : Purpose of Review: Etiologic investigations for adults with intellectual disability (ID) pose a special challenge to many adult neurologists. The adaptability of pediatric guidelines for workup of ID to adult populations has not been clearly established. We review the current recommendations on etiologic workup of ID in children and adults and provide initial guidance for adult neurologists who care for individuals with ID of unknown etiology. Recent Findings: Etiologic workup, including genetic testing, is recommended in individuals with ID of unknown origin. Workup should be guided by a thoughtful history and physical examination, which can help identify certain causes of ID. Summary: Specific diagnoses may help guide management and surveillance of comorbid conditions in individuals with ID. Etiologic investigations of adults with ID include genetic and metabolic testing and brain imaging in the appropriate clinical setting.